A kinetic fluorometric assay of dipeptidyl peptidase IV in viable human blood mononuclear cells - Sedo, A; Krepela, E; Kasafírek, E (Biochimie, 1989)
A continuous-rate fluorometric assay of dipeptidyl peptidase IV (DP-IV) in viable human blood mononuclear cells using 7-(L-glycyl-L-prolylamido)-4-methylcoumarin as the substrate is described. The assay method is accurate, rapid, and highly sensitive for measuring the level of cell-surface bound DP-IV activity in suspension of blood mononuclear cells, as well as of other viable cells bearing this enzyme. We believe that the kinetic assay is suitable for studying the regulation of expression and the role of plasma membrane-bound DP-IV on the cellular level.
Keywords: Spectrometry, Fluorescence; Humans; prolyloligopeptidasy; Prolyl Oligopeptidases; Serine Endopeptidases; dipeptidylpeptidasy a tripeptidylpeptidasy; Dipeptidyl Peptidase 4; fluorescenční spektrometrie; endopeptidasy; Endopeptidases; Leukocytes, Mononuclear; separace buněk; Dipeptidyl-Peptidases and Tripeptidyl-Peptidases; lidé; DNA; Kinetics; dipeptidylpeptidasa 4; serinové endopeptidasy; Cell Separation; leukocyty mononukleární; kinetika